MATHEMATICAL ANALYSIS OF FOREST LAND EFFECT ON AGRICULTURAL CULTURES IN UKRAINE: ECONOMIC CONSEQUENCES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
With the current trend of population growth, an increase in the areas of urban agglomerations and industrial centers, rapid development of transport and tourist infrastructure, the role of forests is increasing in physical, geographical, aesthetic, sanitary and social aspects. World forest reserves annually generate between 20 and 30 billion tonnes of organic biomass, while depositing 30 to 50 billion tonnes of carbon dioxide, while replenishing atmospheric air. In temperate latitudes, 1 ha of forest area during the growing season emits an average of 25 kg of oxygen annually, while 1 ha of tropical forest produces about 60 tonnes of oxygen per year. Thus, providing the necessary conditions for life on our planet, forests are of particular social and ecological general biosphere importance.The goal of the article is to investigate the impact of forest lands on crop yields in Ukraine and to outline the economic consequences of such interaction.Thus, according to the results of our study, the direct impact of forest lands on crop yields can be argued.Taking into account the fact that forest lands are involved in shaping the conditions of cultivation of crops, that is why the destruction of forest plantations leads to deterioration of microclimatic conditions of agricultural production, farmers have to increase the rate of application of mineral fertilizers, solve the problem of optimization of water management. increasing the cost of growing crops. Based on the calculations, it was proved that crop yields increase with decreasing forest cover (R = 0.58 - 0.61), the reason for this being an increase in fertilizer application volumes (R = 0.72).The proposed regression model of the dependence of the amount of mineral fertilizers in growing crops on the area of loss of wood cover - according to Forest Global Watch, will be useful for experts in the field of agricultural production. The application of this model will allow us to predict the likely additional costs of growing crops in the event of deforestation in the region.Such additional costs affect the health of agricultural products. In fact, on the basis of mathematical analysis, we found that the loss of wood cover ultimately affects the increase in average prices of agricultural products (R = 0,63 - 0,78), which is a negative economic factor for the population.
Keywords: математичний аналіз, землі лісогосподарського призначення, урожайність, коефіцієнт кореляції